Communities and knowledge production in archaeology - Roberts, Julia; Shepperd, Kathleen L.; Trigg, Jonathan Ralph; Hansson, Ulf R. (Manchester University Press, 2019)
The dynamic processes of knowledge production in archaeology and elsewhere in the humanities and social sciences are increasingly viewed as the collaborative effort of groups, clusters and communities of researchers rather than the isolated work of so-called 'instrumental' actors. Shifting focus from the individual scholar to the wider social contexts of her work and the dynamic creative processes she participates in, this volume critically examines the importance of informal networks and conversation in the creation of knowledge about the past. Engaging with theoretical approaches such as the sociology and geographies of knowledge and Actor-Network Theory (ANT), and using examples taken from different archaeologies in Europe and North America from the seventeenth to the mid-twentieth century, the book caters to a wide readership, ranging from students of archaeology, anthropology, classics and science studies to the general reader.